Combined CR and S poisoning in solid oxide fuel cell cathodes - Wang, Cheng Cheng (Curtin University, 2016)
The durability and degradation of solid oxide fuel cell (SOFC) cathodes is one of the most critical areas for the commercial viability of the SOFC technologies. Sulfur, most likely from the air stream can accumulate at the cathode side of SOFC stacks, contaminates and degrades the cell performance. The overall objective of this PhD project is to understand sulfur and chromium deposition and poisoning mechanism of SOFC cathode materials under operation conditions